Evaluating the effects of repeated reading and continuous reading using a standardized dosage of words read. Issue 5 (19th February 2019) - Hammerschmidt‐Snidarich, Stephanie M.; Maki, Kathrin E.; Adams, Sarah R.
Abstract: Repeated reading (RR) is a common fluency intervention, but recent studies comparing RR to continuous reading (CR; i.e., wide reading) found no significant differences in effects. This prompts the question of whether the mechanism that improves skills is repeatedly reading portions of connected text, or simply reading connected text. The current study examined the differential effectiveness of RR and CR for increasing oral reading fluency rate (ORF) and comprehension of 40 students in second and third grades, randomly assigned to receive the RR or CR intervention. Students in both conditions received a standardized amount of practice (dosage) in the form of number of words read during each intervention session. All but two participants increased their ORF and there were no significant differences between groups on posttest ORF or broad comprehension. Moreover, students with the highest pretest scores made slightly more growth regardless of condition. Students in the RR group demonstrated significantly higher comprehension of practiced passages and students in the CR condition reported significantly higher levels of intervention acceptability. Implications for reading fluency intervention research and practice are discussed.